Traveler Pro-social Behaviors at Heritage Tourism Sites - Zhu, Peng; Chi, Xiaoting; Ryu, Hyungseo Bobby; Ariza-Montes, Antonio; Han, Heesup (Frontiers in Psychology, 2022)
This study aimed to explain the development of tourists’ pro-social intentions during heritage tourism within the pandemic context by combining the norm activation model (NAM) and two significant variables in the theory of planned behavior (TPB). The quantitative data analysis results indicated that the proposed hypotheses have been partially supported, which resonated and enriched the existing studies on COVID-19-related pro-social tourism and tourist behaviors from a theoretical angle. Based on the research outcomes, the corresponding managerial implications for heritage tourism practitioners and meaningful references for future researchers to promote sustainable and pro-social heritage tourism products have been discussed.